Post-traumatic Acquired Supernumerary Nail - Bhalla Mala; Thami Gurvinder P; Kanwar Amrinder J (Wolters Kluwer Medknow Publications, 2003)
Acquired nail disorders are more common than developmental anomalies. Trauma to the nail unit commonly leads to deformity or dystrophy while a split nail usually occurs as a result of division of nail matrix. An unusual case of split nail resembling a supernumerary nail is being described.